IN VITRO SCREENING OF ANTIOXIDANT AND ANTIAGING POTENTIAL OF CUCUMIS SATIVUS FRUIT EXTRACT - GARG, CHANCHAL; SINGH, RAVINDER; GARG, MUNISH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study was designed to screen the anti-aging and anti-wrinkle potential of Cucumis sativus fruit through in vitro estimation of antioxidant, anti-hyaluronidase, anti-elastase, anti-collagenase/anti-matrix metalloproteinase (MMP)-1, and anti-tyrosinase activity. Methods: Raw juice of cucumber was taken, filtered and fractionated with ethyl acetate and n-butanol. The obtained extracts were then evaluated for their antioxidant potential through 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging assay taking ascorbic acid as positive control and other enzymatic activities in reference to hyaluronidase inhibition, MMP-1/collagenase inhibition, and elastase inhibition taking catechin as reference standard whereas for tyrosinase inhibition the standard used was quercetin. Results: All the evaluations were performed in triplicates and results were noted down. It was observed that aqueous extract of C. sativus fruits showed a maximum DPPH radical scavenging activity (p<0.0001), half-maximal inhibitory concentration (IC50) at a concentration of 122.67 μg/ml. The ethyl acetate fraction of C. sativus fruits exhibited maximum hyaluronidase (p<0.0001), MMP-1/collagenase (p<0.04), and tyrosinase (p<0.04) inhibitory activity, IC50 at a concentration of 59.54, 45.79, and 24.46 μg/ml, respectively. The elastase (p<0.0001) inhibitory activity by n-butanol fraction of C. sativus fruits extract was maximum, IC50 at a concentration of 52.76 μg/ml. Conclusion: A potent anti-aging and anti-wrinkle properties were well demonstrated by C. sativus, as depicted from the results obtained.